(untitled) (The Third Pole: Journal of Geography Education, 2025)
A ghost village is an abandoned human settlement with visible structures due to the failure of economic activity to sustain the villagers. The increasing number of ghost villages in the mountain region is a phenomenon in the Asian highlands due to the outmigration of rural farmers. Rural depopulation is the major cause behind the increasing number of ghost villages in the Mountain and Hill regions in China, India, and Japan. A similar phenomenon is also experienced in Nepal. Thus, this study aims to discuss the number of abandoned villages in Nepal based on population data from the population census and field verification. Changing trend of population of Nepal from 1971 to 2021 and district level changing pattern of population from 2001 to 2021 were analyzed. Ground reality of mountain villages were identified through the field work in 22 villages in the Madi Watershed of Gandaki province of Nepal. The study revealed that a large part of the Mountain and Hill regions have experienced depopulation in recent decades, leaving only the elderly population over 60 years old. In the Madi Watershed of Gandaki Province, nearly 6% of rural settlements in the slope areas have already been abandoned due to the outmigration of rural people to the urban areas and the lower plain. It is estimated that more than 60% of the highland rural settlements will be abandoned within 15 years. The analysis of population dynamics and field study revealed that only a few villages remain along the major route, tourist places, and commercial areas in the slope land areas after 20 to 30 years.